2011
DOI: 10.1093/molbev/msr028
|View full text |Cite
|
Sign up to set email alerts
|

Rampant Gene Loss in the Underground Orchid Rhizanthella gardneri Highlights Evolutionary Constraints on Plastid Genomes

Abstract: Since the endosymbiotic origin of chloroplasts from cyanobacteria 2 billion years ago, the evolution of plastids has been characterized by massive loss of genes. Most plants and algae depend on photosynthesis for energy and have retained ∼110 genes in their chloroplast genome that encode components of the gene expression machinery and subunits of the photosystems. However, nonphotosynthetic parasitic plants have retained a reduced plastid genome, showing that plastids have other essential functions besides pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
245
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(273 citation statements)
references
References 70 publications
14
245
0
Order By: Relevance
“…The prokaryote-type ACCase is composed of four subunits (Gornicki et al, 1997): the a-carboxyltransferase subunit (accA), the biotin carboxyl carrier (accB), and the biotin carboxylase (accC), which are all nucleus encoded, and the b-carboxyltransferase subunit (accD) that is encoded in the plastome (even in the reduced plastomes of parasitic and nonphotosynthetic plants; Wolfe et al, 1992;Bungard, 2004;Delannoy et al, 2011). From a study of 28 plant families, it was observed that, apart from Poaceae, all flowering plants (including Campanulaceae) contain prokaryotic-like ACCase proteins in their chloroplasts (Konishi and Sasaki, 1994;Konishi et al, 1996;Gornicki et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The prokaryote-type ACCase is composed of four subunits (Gornicki et al, 1997): the a-carboxyltransferase subunit (accA), the biotin carboxyl carrier (accB), and the biotin carboxylase (accC), which are all nucleus encoded, and the b-carboxyltransferase subunit (accD) that is encoded in the plastome (even in the reduced plastomes of parasitic and nonphotosynthetic plants; Wolfe et al, 1992;Bungard, 2004;Delannoy et al, 2011). From a study of 28 plant families, it was observed that, apart from Poaceae, all flowering plants (including Campanulaceae) contain prokaryotic-like ACCase proteins in their chloroplasts (Konishi and Sasaki, 1994;Konishi et al, 1996;Gornicki et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a plastid genome and plastid trnE in Polytomella spp., the heme pathway could likely only be completed through the import of a nuclear tRNA for Glu into the plastid from the cytosol, because the Polytomella mitochondrial genome encodes only a single tRNA (an elongator tRNA for Met; Smith et al, 2010). Although plastid tRNA import has yet to be documented, it is thought to occur in various parasitic species (Wolfe et al, 1992;Alkatib et al, 2012a), such as the underground orchid Rhizanthella gardneri (Delannoy et al, 2011). Import of cytosolic tRNAs into mitochondria, however, is well-documented (Duchêne et al, 2009) and, in fact, must occur in the mitochondria of Polytomella spp.…”
Section: The Possibility Of Plastid Genome Lossmentioning
confidence: 99%
“…These examples seem to indicate that ycf1, ycf2, and clpP1 are dispensable. However, their retention in the reduced plastid genomes of parasitic plants (dePamphilis and Palmer, 1990;Funk et al, 2007;McNeal et al, 2007;Delannoy et al, 2011;Logacheva et al, 2011) argues that they are indeed essential, with functions not limited to photosynthesis. This appears to conflict with the model (Bryant et al, 2011) that accD alone is required for embryo development in Arabidopsis.…”
Section: Comparative Genomics and The Loss Of Essential Chloroplast Gmentioning
confidence: 99%